Answer:
85.
Step-by-step explanation:
Let's say that in the beginning he weighted x and at the end he weighted x-y, y being the number of kg he wanted to loose.
first month he lost
y/3
then he lost:
(y-y/3)/3
this is
(2/3y)/3=2/9y
explanation: ((y-y/3) is what he still needed to loose: y minus what he lost already
and then he lost
(y-2/9y-1/3y)/3+3 (the +3 is his additional 3 pounts)
(y-2/9y-1/3y)/3-3=(7/9y-3/9y)/3+3=4/27y+3
it's not just y/3 because each month he lost one third of what the needed to loose at the current time, not in totatl
and the weight at the end of the 3 months was still x-y+3, 3 pounds over his goal weight!
so: x -y/3-2/9y-4/27y-3=x-y+3
we can subtract x from both sides:
-y/3-2/9y-4/27y-3=-y+3
add everything up:
-19/27y=-y+6
which means
-19/27y=-y+6
y-6=19/27y
8/27y=6
4/27y=3
y=20.25
so... that's how much he wanted to loose, but he lost 3 less than that, so 23.25
ps. i hope I didn't make a mistake in counting, let me know if i did. In any case you know HOW to solve it now, try to do the calculations yourself to see if they're correct!
She accumulated an average rate of 12 CDs each year. You find this by subtracting 47 from 83 which gives you 36, dividing it by 3, which gives you 12.